Effect of three modes of linear thermal forcing on convective flow and heat transfer in rectangular cavities. (February 2020) - Liu, Yang; Huang, Han
Highlights: Convective flow in rectangular finned and non-finned cavities subject to three thermal forcing is investigated by DNS. The convective flow with s  > 0 is essentially similar to the classic homogenously heating problem, i.e. the s  = 0 heating mode. The s  < 0 heating mode can best promote the convective flow in the cavities. 'Neutral buoyant effect' is found for the s  < 0 heating mode and the heat transfer performance is therefore reduced. Abstract: The convective flow in rectangular cavities with different linear thermal forcing at the sidewalls is investigated by DNS (direct numerical simulation) in the present study. A non-finned cavity and a cavity with an adiabatic horizontal thin fin attached to the middle of both sidewalls are modelled. Three heating modes are considered and calculated, i.e. s  < 0, s  = 0 and s  > 0 thermal forcing respectively and six Rayleigh numbers ranging from 1.15 × 10 8 to 3.68 × 10 9 are examined. It demonstrates that compared to the s  = 0 case, which is the classic homogenously heating problem, the thermal boundary layer flow as well as the convective flow in the cavities is strengthened for the s  < 0 heating mode and weakened for the s  > 0 heating mode. It is found from the finned cavity calculation that, for all the three thermal forcing considered, significant flow oscillation is observed on top the thin fin which in turn causes strong disturbances in its downstream flow adjacent to the sidewalls. The present results suggest that compared to simply increasing the Rayleigh number of the flow, switching the heating mode to s  < 0 is potentially a shortcut for the purposes of promoting the flow. However, it is further revealed that due to the existence of the so called neutral buoyant effect at the sidewalls, the heat transfer associated with the s  < 0 scenario is lower than the other two heating modes.